2012
DOI: 10.1111/exd.12018
|View full text |Cite
|
Sign up to set email alerts
|

Expressions and inhibitory functions of CD300a receptors on purified human basophils

Abstract: The inhibitory myeloid immunoglobulin receptor CD300a (IRp60) has been shown to downregulate mast cell and eosinophil activities, thereby serving as a potential target for inhibiting allergic effector cell input in allergy. Our aims were to study the expression and functional properties of this receptor in purified human basophils, cells that crucially contribute to Th2-type immunity and allergy. Basophils homogeneously expressed CD300a as well as the inhibitory receptor CD200R on their cell surface, and these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“…Furthermore, immunoprecipitation of CD300a from human mast cells that were treated with Kit-CD300a, a bispecific Ab fragment linking Kit with CD300a, induced its tyrosine phosphorylation and the recruitment of SHIP but not SHP-1 (53). Triggering of CD300a with mAbs induced weak phosphorylation of SHIP-1 on human basophils, but the phosphorylation status of SHP-1 and SHP-2 was not tested (21). In a mouse B cell line, coligation of the BCR with anti-mouse IgG and Fc-CD300a, a chimeric molecule consisting of the extracellular and transmembrane domains of FcgRIIB and the cytoplasmic domain of mouse CD300a, resulted in the association of the intracellular tail of CD300a with SHP-1, SHP-2, and SHIP (30).…”
Section: Mechanisms Of Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, immunoprecipitation of CD300a from human mast cells that were treated with Kit-CD300a, a bispecific Ab fragment linking Kit with CD300a, induced its tyrosine phosphorylation and the recruitment of SHIP but not SHP-1 (53). Triggering of CD300a with mAbs induced weak phosphorylation of SHIP-1 on human basophils, but the phosphorylation status of SHP-1 and SHP-2 was not tested (21). In a mouse B cell line, coligation of the BCR with anti-mouse IgG and Fc-CD300a, a chimeric molecule consisting of the extracellular and transmembrane domains of FcgRIIB and the cytoplasmic domain of mouse CD300a, resulted in the association of the intracellular tail of CD300a with SHP-1, SHP-2, and SHIP (30).…”
Section: Mechanisms Of Signalingmentioning
confidence: 99%
“…Naive B cells express low levels of CD300a, whereas memory B cells and plasma cells express variable levels, and germinal center B cells are negative for CD300a cell surface expression (16). In the myeloid lineage, CD300a is detected on the surface of plasmacytoid dendritic cells (pDCs), myeloid dendritic cells (mDCs), monocytes, macrophages, neutrophils, eosinophils, basophils, and mast cells (13,(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Regulation Of Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19][20][21] CD300a plays a role in the regulation of immune responses, acting predominantly as an inhibitory receptor. Its engagement by an agonist mAb decreases NK cell cytotoxicity, 14,22 inhibits IgE-induced mast cell and basophil degranulation, 17,21 T-cell proliferation and IFNg secretion, 19 and B-cell receptor-mediated signaling, 20 reduces FcgRIIatriggered reactive oxygen species production and Ca 2+ flux in neutrophils, 16 and suppresses eosinophil survival, migration and inflammatory mediator production triggered by eotaxin, IL-5 and granulocyte macrophage colony-stimulating factor. 18 Furthermore, in vivo studies in mice with bispecific Abs have shown that CD300a triggering can reverse tissue remodeling and airway inflammation in a model of asthma, 23 and abrogate IgE-mediated allergic reactions 17 and stem cell factorinduced cutaneous anaphylaxis.…”
Section: Introductionmentioning
confidence: 99%